2017
DOI: 10.1088/1757-899x/205/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Property Analysis on Sandwich Structured Hybrid Composite Made from Natural Fibre, Glass Fibre and Ceramic Fibre Wool Reinforced with Epoxy Resin

Abstract: Natural fibre composites find wide range of applications and usage in the automobile and manufacturing industries. They find lack in desired properties, which are required for present applications. In current scenario, many developments in composite materials involve the synthesis of Hybrid composite materials to overcome some of the lacking properties. In this present investigation, two sandwich structured hybrid composite materials have been made by reinforcing Aloe Vera-Ceramic Fibre Wool-Glass fibre with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Fiber diameter with 3mm shows better tensile strength, flexural property and impact property than others. Bharat et al [20] has prepared two different composites first one is Aloe Vera-Ceramic Fiber Wool-Glass fiber with Epoxy resin matrix and other one is Sisal fiber-Ceramic Fiber Wool-Glass fiber with Epoxy resin matrix. Tensile strength, flexural strength and impact strength of Sisal fiber-Ceramic Fiber Wool-Glass fiber with Epoxy resin is more than Aloe Vera-Ceramic Fiber Wool-Glass fiber with Epoxy resin.…”
Section: Mechanical Properties Of Natural and Synthetic Fiber Based Hybrid Polymer Compositesmentioning
confidence: 99%
“…Fiber diameter with 3mm shows better tensile strength, flexural property and impact property than others. Bharat et al [20] has prepared two different composites first one is Aloe Vera-Ceramic Fiber Wool-Glass fiber with Epoxy resin matrix and other one is Sisal fiber-Ceramic Fiber Wool-Glass fiber with Epoxy resin matrix. Tensile strength, flexural strength and impact strength of Sisal fiber-Ceramic Fiber Wool-Glass fiber with Epoxy resin is more than Aloe Vera-Ceramic Fiber Wool-Glass fiber with Epoxy resin.…”
Section: Mechanical Properties Of Natural and Synthetic Fiber Based Hybrid Polymer Compositesmentioning
confidence: 99%
“…The tensile strength and hardness of natural fiber hybrid materials depended on the glass fiber content, and increased with weight concentration. On the other hand, in paper [48], two sandwich-structured hybrid composite materials were fabricated from Aloe vera fiber, ceramic fiber wool, glass fiber with the epoxy polymer matrix and from sisal fiber, ceramic fiber wool, glass fiber with epoxy polymer matrix. The mechanical analysis confirmed that the sisal fiber reinforced laminates had better mechanical properties than the Aloe vera fiber reinforced laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigations have been carried out to enhance the adhesion between the fibres and the polymeric matrix through adopting some techniques such as reinforcement fibre surface modification and matrix modification [109][110][111]. To this end, the fibres are subjected to various chemical treatments [112,113], such as alkali treatment [114][115][116][117], silane treatment [118][119][120][121][122][123], esterification [124][125][126][127], acid treatment [128] or hybridization with different fibres [129][130][131][132][133][134][135][136], before reacting with the matrix materials.…”
Section: Mechanical Properties Of the Biocompositesmentioning
confidence: 99%